Assessment of anti-CD20 antibody pre-treatment for augmentation of CAR-T cell therapy in SIV-infected rhesus macaques - Pampusch, Mary S.; Sevcik, Emily N.; Quinn, Zoe E.; Davey, Brianna C.; Berg, James M.; Gorrell-Brown, Ian; Abdelaal, Hadia M.; Rakasz, Eva G.; Rendahl, Aaron; Skinner, Pamela J. (Frontiers in Immunology, 2023)
Abstract During chronic HIV and SIV infections, the majority of viral replication occurs within lymphoid follicles. In a pilot study, infusion of SIV-specific CD4-MBL-CAR-T cells expressing the follicular homing receptor, CXCR5, led to follicular localization of the cells and a reduction in SIV viral loads in rhesus macaques. However, the CAR-T cells failed to persist. In this study we treated additional animals with CAR-T cells and preconditioned a set of animals to promote CAR-T cell engraftment. We hypothesized that temporary disruption of follicles with anti-CD20 antibody would create space for CAR-T cell engraftment and lead to increased abundance and persistence. We evaluated four groups of animals: untreated, CAR-T cell treated, CD20 depleted, and CD20 depleted/CAR-T cell treated. All animals were SIVmac239-infected and ART-suppressed. With combined data from our pilot study, we found 71% of non depleted CAR-T treated and 14% of untreated animals had viral loads below 1000 virus copies/ml at two months post-treatment. In the depletion study, anti-CD20 was infused a week prior to CAR-T infusion and cessation of ART. Siltuximab, to prevent cytokine release syndrome (CRS), was deemed necessary and initiated with the depleted animals. Anti-CD20 antibody treatment led to temporary depletion of CD20+ cells in blood and partial depletion in lymph nodes. CAR-T cells accumulated in and around lymphoid follicles, were Ki67+, and increased in numbers in follicles from 2 to 6 days post-treatment, with a median of 15.2-fold in depleted/CAR-T treated animals compared to 8.1-fold in CAR-T treated animals. After rapid expansion, CAR-T cells became undetectable in depleted/CAR-T but not CAR-T treated animals. An anti-CAR antibody response was detected. These findings bolster earlier studies showing CD4-MBL-CAR/CXCR5 T cells can be safe and potentially efficacious in promoting sustained remission of SIV infection. The results also suggest that pre-treatment with anti-CD20 antibody may lead to a robust expansion of therapeutic cells; however, further optimization is needed to promote survival of the CAR-T cells after expansion, and for safety, CRS responses must be prevented. These studies provide important insights into cellular immunotherapy and suggest future studies for improved outcomes.